Guaranteed Trajectory Tracking under Learned Dynamics with Contraction Metrics and Disturbance Estimation - Pan Zhao; Ziyao Guo; Yikun Cheng; Aditya Gahlawat; Hyungsoo Kang; Naira Hovakimyan (Robotics, 2024)
This paper presents a contraction-based learning control architecture that allows for using model learning tools to learn matched model uncertainties while guaranteeing trajectory tracking performance during the learning transients. The architecture relies on a disturbance estimator to estimate the pointwise value of the uncertainty, i.e., the discrepancy between a nominal model and the true dynamics, with pre-computable estimation error bounds, and a robust Riemannian energy condition for computing the control signal. Under certain conditions, the controller guarantees exponential trajectory convergence during the learning transients, while learning can improve robustness and facilitate better trajectory planning. Simulation results validate the efficacy of the proposed control architecture.